Estudo de propriedades da resina acrílica termoativada por energia de micro-ondas frente às variações nos procedimentos de inclusão - Paes Junior,Tarcisio José de Arruda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
On heat cured acrylic resins by microwaves energy the action of electromagnetic waves on methylmethacrylate promote the polymerization process. However, part of this energy is absorbed by the gypsum present in the flask and the function of this gypsum is to maintain the characteristics of specimen, nevertheless is unknown in the literature as the amount of water present in this gypsum affects the characteristics of acrylic resin. The proposal of this study was verified if dried gypsum influenced in some properties of the acrylic resins thermally activated by microwaves: presence of porosity, microhardness, roughness, flexural strength and dimensional change. Two different types of acrylic resin for complete denture were utilized: Lucitone 550 e Vipi-Wave and groups were formed: Lucitone 550, polymerization by microwave energy without gypsum treatment; Lucitone 550, polymerization by microwave energy with pretreatment gypsum; Vipi-Wave by microwave energy without gypsum treatment; Vipi Wave, polymerization by microwave energy with pretreatment gypsum; Lucitone 550 control group polymerization in hot water bath. For both situations were performed analysis of microhardness and porosity three different metallic shaped specimens were formed with followed dimensions: 2,0x2,0x2,0cm (8cm3); 2,0x2,0x1,0 (4cm3) e 2,0x2,0x0,5 (2cm3). Standardized wax specimens was used to prepare groups (n=9) and included in glass fiber flasks. The gypsum dry was made by microwave oven cycle (10min and 600W) and then the flasks were maintained in dry oven during two hours. Polymerizations of specimens were made and then polished. Wax patterns #7 obtained from the metal were embedded in plastic flask and following the processes of pressing and polymerization of the resin according to established groups. To evaluate the flexural strength, specimens 65mm x 10mm x 3.0mm from metallic patterns in bar format were made. ...

A resina acrílica ativada por micro-ondas tem, na ação das ondas eletromagnéticas sobre o metilmetacrilato a ativação e desencadeamento do processo de polimerização, entretanto, parte desta energia é absorvida pelo gesso presente na mufla e que mantem as características da peça a ser confeccionada, entretanto é desconhecido na literatura o quanto a quantidade de água presente neste gesso afeta as características da resina acrílica. Diante disto, o objetivo deste trabalho foi verificar se a secagem prévia do gesso presente na mufla influência, quando da polimerização por energia de micro-ondas, em algumas propriedades: presença de porosidades, dureza, rugosidade, resistência a flexão e alteração dimensional. Para execução destes experimentos duas resinas acrílicas de ativação térmica empregadas em bases de próteses totais foram empregadas: Lucitone 550 e Vipi-Wave, e os seguintes grupos estabelecidos (n=9): Grupo LM - Lucitone 550, polimerização em micro-ondas, sem tratamento prévio do gesso na mufla; Grupo LMS - Lucitone 550, polimerização em micro-ondas, com tratamento prévio do gesso (dissecação); Grupo VM - Vipi-Wave, polimerização em microondas, sem tratamento prévio do gesso de inclusão; Grupo VMS - Vipi-Wave, polimerização em micro-, ondas, com tratamento prévio do gesso de inclusão (gesso dissecado); Grupo LC - Lucitone 550, em banho de água aquecida (controle). Com relação à avaliação da dureza, rugosidade e porosidade o mesmo tipo corpo de prova foi utilizado onde se confeccionou três padrões metálicos no formato geométrico de um paralelogramo, com dimensões respectivamente de 2,0x2,0x2,0cm (8cm3), 2,0x2,0x1,0 (4cm3) e 2,0x2,0x0,5 (2cm3). Padrões em cera nº 7 obtidos a partir dos metálicos foram incluídos em muflas plásticas para microondas e na sequência, os processos de prensagem e polimerização da resina...
Keywords: Resinas acrílicas; Porosidade; Microondas; Materiais dentários; Dental materials